Predictability of Analyst Earnings Forecast Errors and Institutional and Individual Investors' Reactions to Earnings News. (October 2021) - Bhattacharya, Nilabhra; Olsson, Per; Park, Hyungshin
We decompose analysts' earnings forecast error into predictable and unpredictable components and investigate individual vis-à-vis institutional investors' reactions to each of these components. We find that in the immediate post-earnings announcement window, only individuals under-react to the predictable component, while both individuals and institutions under-react to the unpredictable component. The price drift in this window is driven primarily by investors' under-reaction to the unpredictable component. This drift remains highly significant in larger firms and intensifies in firms with complex financial reports, suggesting that it likely represents the slow and noisy process of price discovery. Around the next quarterly earnings announcement, only individuals under-react to the previous quarter's predictable component, and this fixation drives the entire price drift in this window. This drift disappears in larger firms and gets exacerbated in firms with greater forecast error autocorrelations, suggesting that it is likely attributable to incomplete processing of earnings information by individuals.